2006
DOI: 10.1093/nar/gkl846
|View full text |Cite
|
Sign up to set email alerts
|

Replication in mammalian cells recapitulates the locus-specific differences in somatic instability of genomic GAA triplet-repeats

Abstract: Friedreich ataxia is caused by an expanded (GAA·TTC)n sequence in intron 1 of the FXN gene. Small pool PCR analysis showed that pure (GAA·TTC)44+ sequences at the FXN locus are unstable in somatic cells in vivo, displaying both expansions and contractions. On searching the entire human and mouse genomes we identified three other genomic loci with pure (GAA·TTC)44+ sequences. Alleles at these loci showed mutation loads of <1% compared with 6.3–30% for FXN alleles of similar length, indicating that somatic insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Using a plasmid-based model system, it has been shown that the replication fork stalls at expanded GAA repeats (Chandok et al, 2012; Krasilnikova and Mirkin, 2004) and that altered replication fork progression results in repeat instability (Cleary et al, 2002; Pelletier et al, 2003; Rindler et al, 2006; Shishkin et al, 2009). It is still unknown, however, how the replication fork proceeds through the endogenous FXN locus in the native chromatin environment and whether the replication machinery stalls at the GAA repeats in FRDA cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a plasmid-based model system, it has been shown that the replication fork stalls at expanded GAA repeats (Chandok et al, 2012; Krasilnikova and Mirkin, 2004) and that altered replication fork progression results in repeat instability (Cleary et al, 2002; Pelletier et al, 2003; Rindler et al, 2006; Shishkin et al, 2009). It is still unknown, however, how the replication fork proceeds through the endogenous FXN locus in the native chromatin environment and whether the replication machinery stalls at the GAA repeats in FRDA cells.…”
Section: Resultsmentioning
confidence: 99%
“…In plasmid-based experiments, an increase in instability of particular expansions was detected when TTC repeats were located on the lagging strand template (3’−5’ direction at the endogenous locus) (Rindler et al, 2006). To determine an accurate direction of the replication fork, we calculated the percentage of molecules with replication forks in either the 5’−3’ or 3’−5’ direction progressing through the GAA repeats in control hESCs, control iPSCs, FRDA iPSCs and FRDA fibroblasts (Figure 3F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Replication has been shown to influence GAA·TTC repeat stability in previous model systems [24], [28][30],[39]. To analyze the influence of replication on GAA·TTC expansion in our cell lines, we sought to alter cell division rates during culturing and analyze the influence on GAA·TTC stability (Figure 4).…”
Section: Resultsmentioning
confidence: 99%